Optimization of a cryoprotective medium and survival of freeze-dried Bifidobacterium infantis 20088 throughout storage, rehydration and gastrointestinal tract transit for infant formula probiotic applications - Fatemeh, Shamekhi; Mustafa, Shuhaimi; Ariff, Arbakariya; Abd Manap, Mohd Yazid (Academic Journals, 2011)
Supplementations of formulae with synbiotic compounds of human milk have shown to be able to decrease several gut-related diseases in formula fed infants. This study was carried out to develop a synergistic cryoprotective drying medium for infant formulae probiotic application. Response surface methodology (RSM) was employed to optimize the concentrations of skim milk and prebiotics for improvement of the cell survival of Bifidobacterium infantis 20088, during freeze-drying. The optimal composition was found to be 2.8% prebiotics blended with 16.1% skim milk which could protect 47.63% of cells' viability. No significant difference (p > 0.05) between the predicted and experimental values validated the model adequacy. Then, the protective effects of optimal composition on the survival of freeze-dried cells were evaluated through different conditions of rehydration, storage and simulated gastrointestinal tract (GIT) as compared to cells dried in phosphate buffer (control). After 120 days storage of freeze-dried stationary phase cells at 4°C, there was 2.33 log (CFU/ml) improvement in the viability of cells as compared to control. With increasing temperature to 25°C, the protective effect of optimized medium was more apparent. Direct rehydration with water led to 0.65 log (CFU/ml) increment in the mortality rate of freeze-dried cells as compared to rehydration with skim milk solution. Also, the mortality rate of cells after sequential incubation in simulated GIT conditions including gastric conditions (pH 3.0 and 4.0, 90 min) and intestinal conditions (pH 7.5, 5 h) were reduced by 1.81 and 0.35 log (CFU/ml), respectively, as compared to the control.